Endoscopic Decompression of Recurrent Sigmoid Volvulus in Pregnancy - Nathaly Cortez MD; Manuel Berzosa MD; Kiranmayi Muddasani MD; Kfir Ben-David MD, FACS (SAGE Publishing, 2020)
Sigmoid volvulus is a rare condition seen during pregnancy with high maternal and fetal morbidity and mortality. We report a case of a young 26-year-old woman, primipara, in her third trimester who presented with recurrent sigmoid volvulus at both 30 and 32 weeks of gestation. She underwent successful repetitive endoscopic decompression on both admissions with uneventful recovery. Endoscopic evaluation is safe in pregnancy and uncomplicated volvulus. It allows for diagnostic confirmation and assessment of complications; and it has successful outcomes in the presence of a multidisciplinary team.